Comparative efficacy of certain extenders on preservation of liquid boar semen - KAUR, J; SINGH, A K; DHINDSA, S S; SINGH, P; DAS, S K (The Indian Journal of Animal Sciences, 2023)
This study was carried out to compare the efficacy of certain liquid semen extenders for boar semen preservation. Semen ejaculates (n=30) from three boars (one ejaculate/boar/week) stationed at University pig farm, Ludhiana were collected using dummy sow and extended (1:4) in lactose-sodium salt of EDTA-Egg yolk (LSEEY); glucose sodium salt of EDTA-potassium sodium tartrate-sodium citrate (GEPS); and Modena (MOD). The extended semen was kept at 17°C up to 120 h in a BOD incubator. The semen was assessed for various sperm characteristics and lipid peroxidation at 0, 24, 48, 72, 96 and 120 h of preservation. The results revealed significantly higher percentage of sperm motility, viability, plasma membrane integrity and acrosome integrity in semen extended with MOD thanin GEPS and LSEEY at different preservation times. The mean percentage of in vitro capacitation/acrosome reacted spermatozoa was significantly higher in MOD as compared to GEPS and LSEEY at 96 h and 120 h of storage period. In all the extenders, the mean percentage of most sperm attributes decreased progressively as the storage period increased. Correspondingly, the MDA levels were lower in MOD than in their contemporary extenders at all hours of preservation. In conclusion, Modena exhibited improved sperm parameters and reduced oxidative stress for liquid preservation of boar semen.